White-collar crime: Detection and neutralization in religious organizations - Gottschalk, Petter (International journal of police science & management, 2017)
Policing religious organizations presents challenging situations. When there is suspicion of financial crime by white-collar criminals, secrecy and trust represent obstacles to law enforcement. This article discusses the lack of detection and neutralization techniques often applied in religious organizations. There may be too much trust, too much freedom, too much individual authority, too little scepticism, too much loyalty and too little control of the financial side in religious organizations. There may be no empirical evidence for the proposition that religion has a deterrent effect on crime, although sociologists and criminologists have long recognized potential links between religious belief and delinquent behaviour.